6n+7=-5+3n

Simple and best practice solution for 6n+7=-5+3n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6n+7=-5+3n equation:



6n+7=-5+3n
We move all terms to the left:
6n+7-(-5+3n)=0
We add all the numbers together, and all the variables
6n-(3n-5)+7=0
We get rid of parentheses
6n-3n+5+7=0
We add all the numbers together, and all the variables
3n+12=0
We move all terms containing n to the left, all other terms to the right
3n=-12
n=-12/3
n=-4

See similar equations:

| 9(x-99)-2(x+66)=55-4(x-77) | | (4x+10)+(6x-10)=180 | | 1x+7=2x+6 | | 3(x+15)-2(-x+10)=15 | | 7(3+2x)-17-10x=29-x | | 3/16+y=11/16 | | 3x-1=1x+15 | | m=10+9 | | 5(x+16)=x+4 | | 2x+x+1/2x=49 | | -4X+3=0.5(-8x+8) | | 2x–5=3x+4 | | 4x2+5=12x | | 2x-5x+3=9 | | 6(7x+2)=42x-1 | | 63-8x=63-x | | x-7/18=1/3 | | (x+24)=35 | | 2=6b-1=4b | | 3(9-3x)=-9 | | 5x-24=x-16 | | -2c2-9c-2=-3c2 | | x-3.7=8.6 | | -2c-9c-2=-3c2 | | 6/7a=6 | | 5/13-2x=-8/11 | | 1+6x=12=4x+5+4x | | p+8=4.1 | | 8(2x-4)-2x=24 | | 4x+24=x+12 | | 2t-3t=7 | | 1.6x+4.2=9.8 |

Equations solver categories